2021
DOI: 10.1111/agec.12619
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon sequestration in French agricultural soils: A spatial economic evaluation

Abstract: Soil organic carbon sequestration measures entail costs to farmers with different individual characteristics and located in different areas. A cost‐effective analysis taking into account these heterogeneities is crucial for developing effective public policy aimed at increasing carbon sequestration. We undertake such an analysis focusing on three soil organic carbon sequestration measures: no‐till, extension of temporary grasslands, and hedgerows. Through an optimization model applied to France, our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Economic incentives to encourage landholder adoption of SOC sequestration practices may take the form of payments or subsidies for increases in SOC stocks or penalties, such as taxes for SOC losses. A study of land use in France sought to compare the cost-effectiveness of approaches based on either payments to compensate for costs of implementing better practice, or taxes (Bamière et al 2021). The study, which examined three SOC sequestration measures -no-till, extension of temporary grasslands and hedgerows -found a disparity between net SOC sequestration and costs of implementation.…”
Section: Economic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic incentives to encourage landholder adoption of SOC sequestration practices may take the form of payments or subsidies for increases in SOC stocks or penalties, such as taxes for SOC losses. A study of land use in France sought to compare the cost-effectiveness of approaches based on either payments to compensate for costs of implementing better practice, or taxes (Bamière et al 2021). The study, which examined three SOC sequestration measures -no-till, extension of temporary grasslands and hedgerows -found a disparity between net SOC sequestration and costs of implementation.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Hedgerows and extended pasture phases in mixed crop/pasture systems resulted in sequestration of, respectively, 14.5 and 1.6 Mt CO 2 -e, but very different average costs of €75/t CO 2 -e sequestered for the hedgerow option but -€259/t CO 2 -e in the case of extended pasture phases. Bamière et al (2021) found that increasing the carbon price from €50 to €100 per t CO 2 -e shifted the viability of actions and the dominance of farming enterprise participation. At the higher carbon price, the area of fallow land entering the scheme increased at the expense of the least-cost carbon storage option of temporary grasslands.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Previous research has estimated the supply curve for carbon sequestration using mathematical programming models (Adams et al., 1993; Bamière et al., 2021; Beach et al., 2008; Frey et al., 2013; Parks & Hardie, 1995; Richards et al., 1993; Schneider & McCarl, 2006), econometric models (Lubowski et al., 2006; Newell & Stavins, 2000; Plantinga & Wu, 2003; Plantinga et al., 1999; Stavins, 1999), or a mix of programming and econometric models (Antle et al., 2003). Some of the previous work depends on stated preferences for how landowners would respond to a hypothetical policy (Adams et al., 1993; Parks & Hardie, 1995; Richards et al., 1993; Van Kooten et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al (2020) estimate an increase in the selling price of the products of 0.4 EUR•kg -1 due to improved fruit quality and increased product value by using more environmentally friendly techniques. On the other hand, there may be other benefits derived from the provision of other ecosystem services by hedgerows, such as carbon sequestration, which is estimated to provide additional soil carbon storage of 0.15 tonnes per ha per year (Bamière et al 2021), or enhanced pollination, which can be increased by up to 36% (Morandin et al 2016). However, installing hedgerows can lead to a reduction in crop yields, estimated at 1.2% by Bamière et al (2021).…”
mentioning
confidence: 99%
“…On the other hand, there may be other benefits derived from the provision of other ecosystem services by hedgerows, such as carbon sequestration, which is estimated to provide additional soil carbon storage of 0.15 tonnes per ha per year (Bamière et al 2021), or enhanced pollination, which can be increased by up to 36% (Morandin et al 2016). However, installing hedgerows can lead to a reduction in crop yields, estimated at 1.2% by Bamière et al (2021). In any case, this practice is not very widespread among farmers who produce in greenhouses because they consider it best to maintain scarce vegetation around their farms because they believe this reduces the risk of pest infestations (Messelink et al 2021).…”
mentioning
confidence: 99%